2014
DOI: 10.1523/jneurosci.1111-14.2014
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Deterioration and Functional Compensation in ALS Measured with fMRI Using an Inhibitory Task

Abstract: Amyotrophic lateral sclerosis (ALS) is characterized by degeneration of upper and lower motor neurons, resulting in progressive weakness and muscle atrophy. Recent studies suggest that nondemented ALS patients can show selective cognitive impairments, predominantly executive dysfunction, but little is known about the neural basis of these impairments. Oculomotor studies in ALS have described deficits in antisaccade execution, which requires the implementation of a task set that includes inhibition of automatic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
63
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(72 citation statements)
references
References 88 publications
9
63
0
Order By: Relevance
“…This explanation is further supported by the trend for a negative correlation between MFG activation increases and reaction time increases during the sustained attention task, which indicates that subjects with greater brain activation increases in the task-positive network were more resistant to the TOT effects. Increased brain activations from the first to last quintile of the PVT are also consistent with previous studies showing that enhanced brain activation or recruitment of additional neural resources may provide a compensatory mechanism to help people maintain normal cognition (Elman et al, 2014; Witiuk et al, 2014). …”
Section: Discussionsupporting
confidence: 91%
“…This explanation is further supported by the trend for a negative correlation between MFG activation increases and reaction time increases during the sustained attention task, which indicates that subjects with greater brain activation increases in the task-positive network were more resistant to the TOT effects. Increased brain activations from the first to last quintile of the PVT are also consistent with previous studies showing that enhanced brain activation or recruitment of additional neural resources may provide a compensatory mechanism to help people maintain normal cognition (Elman et al, 2014; Witiuk et al, 2014). …”
Section: Discussionsupporting
confidence: 91%
“…Although cognitively impaired ALS patients are predictably under‐represented in demanding functional neuroimaging tasks, comparatively reduced activation in the dorsolateral prefrontal cortex has been demonstrated [Witiuk et al, 2014], while other frontal regions reveal increased activation during inhibition of prepared manual movements [Mohammadi et al, 2015]. The present finding of abnormal beta power in AGCs during successful inhibition was limited to posterior cortical regions in the context of task‐induced inferior and pre‐frontal activity.…”
Section: Discussionmentioning
confidence: 49%
“…In addition to structural abnormalities, fMRI studies have demonstrated increased cortical activity in patients with ALS performing motor tasks [75, 76], as well as aberrations in the BOLD response to cognitive tasks, such as antisaccade [77] or phonemic fluency tasks [78]. A number of fMRI studies investigating differences between patients with ALS and controls at rest have furthermore revealed functional connectivity abnormalities within the sensorimotor network, although some studies reported reduced functional connectivity in ALS [7981], others increased motor network coherence [71, 82], and others a mixed picture [83, 84].…”
Section: Emerging Imaging Biomarkers In Alsmentioning
confidence: 99%